An evaluation system for financial compensation in traditional Chinese medicine services. Issue 5 (October 2015) - Dou, Lei; Yin, Ai-Tian; Hao, Mo; Lu, Jun
Highlights Develop a comprehensive evaluation system for TCM services financial compensation. Economic was the most important factor affecting TCM development. Acupuncture, Moxibustion, Massage, and TCM Orthopedics should be compensated priority.